2013
DOI: 10.1158/1078-0432.ccr-12-3325
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miR-21 InhibitsIn VitroandIn VivoMultiple Myeloma Cell Growth

Abstract: Purpose Deregulated expression of microRNAs (miRNAs) plays a role in the pathogenesis and progression of multiple myeloma (MM). Among upregulated miRNAs, miR-21 has oncogenic potential and therefore represents an attractive target for the treatment of MM. Experimental design Here, we investigated the in vitro and in vivo anti-MM activity of miR-21 inhibitors. Results Either transient enforced expression or lentivirus-based constitutive expression of miR-21 inhibitors triggered significant growth inhibition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
165
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 199 publications
(179 citation statements)
references
References 51 publications
9
165
0
Order By: Relevance
“…Its relevance in multiple myeloma was first suggested by Loffler and colleagues, who showed that miR-21 transcription is controlled by IL-6 through a mechanism involving STAT3, and that its ectopic expression gives independence from the IL-6-growth stimulus (33). More recently, we provided evidence that antagonism of miR-21 exerts antimultiple myeloma activity in vitro and in vivo (34). Importantly, miR-21 expression in multiple myeloma cells was significantly enhanced by the adherence of cells to human BM stromal cells (hBMSC), and anti-multiple myeloma activity of miR-21 inhibitors was exerted also in the context of BM milieu, antagonizing the protective role of BMSCs on multiple myeloma cells (34).…”
Section: Discussionmentioning
confidence: 53%
“…Its relevance in multiple myeloma was first suggested by Loffler and colleagues, who showed that miR-21 transcription is controlled by IL-6 through a mechanism involving STAT3, and that its ectopic expression gives independence from the IL-6-growth stimulus (33). More recently, we provided evidence that antagonism of miR-21 exerts antimultiple myeloma activity in vitro and in vivo (34). Importantly, miR-21 expression in multiple myeloma cells was significantly enhanced by the adherence of cells to human BM stromal cells (hBMSC), and anti-multiple myeloma activity of miR-21 inhibitors was exerted also in the context of BM milieu, antagonizing the protective role of BMSCs on multiple myeloma cells (34).…”
Section: Discussionmentioning
confidence: 53%
“…In addition, the tumor suppressor Spry2 was revealed to be negatively correlated with miR-21 expression in myeloma cells. Inhibition of miR-21 led to upregulation of PTEN and downregulation of phosphorylated AKT in xenografts of myeloma (47,48). These results suggested that miR-21 is important in hematological malignancies.…”
Section: Mir-21 and Hematological Malignanciesmentioning
confidence: 72%
“…In the last few years, a wealth of studies has shown deep dysregulation of miRNAs in human cancers, including multiple myeloma (3). Importantly, replacement of downregulated tumor suppressor (TS) miRNAs (4,5) or inhibition of oncogenic miRNAs (6)(7)(8) have demonstrated therapeutic value in multiple myeloma preclinical settings. A subclass of TSmiRNAs, named epi-miRNAs, is emerging as novel epigenetic regulators, which target and downregulate the expression of DNA methyltransferases (DNMT), histone deacetylases (HDAC), or components of the polycomb repressor complexes, thus representing relevant tools to revert epigenetic aberrations.…”
Section: Introductionmentioning
confidence: 99%